The Influence of Audit Fees, Audit Tenure, Company Size and Managerial Ownership on Audit Quality - Apriani, Rosa; Herawaty, Netty; Friyani, Rita (PT FORMOSA CENDEKIA GLOBAL, 2024)
Every company must provide quality financial reports presented in the form of company financial statements or with accounting information. Public accountants are needed to find misrepresentations or fraud in financial statements and reduce the possibility of this happening. This research aims to provide an explanation and analysis of the effect of audit fees, audit duration, company size and managerial ownership on audit quality in transportation and logistics sector companies listed on the IDX in 2016-2022. This study involved 63 observations, each with 9 samples and 30 populations. Data analysis was carried out using descriptive statistics, classical assumption tests and multiple linear regression analysis using SPSS 25 software. The results of the study concluded that audit fees and company size had an effect, but audit tenure and managerial ownership did not.